2016
DOI: 10.1159/000448042
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Retinal Astrocytic Tumor (Focal Nodular Gliosis): A Case Report

Abstract: Purpose: To report the clinical and histopathological findings of a reactive retinal astrocytic tumor (RRAT) that progressed to massive retinal gliosis. Observations: The patient presented with an elevated, white-yellow retinal mass and extensive retinal exudation in the left eye. Progressive enlargement of the mass and proliferative vitreoretinopathy eventually led to phthisis bulbi and enucleation. Histologically, the mass showed a predominant astrocytic component with intense glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A boy with congenital unilateral microphthalmos presented with an orbital mass with histologic features of pilocytic astrocytoma and/or retinal gliosis. Using light microscopy, low-grade intraocular astrocytoma is indistinguishable from massive retinal gliosis 1, 2, 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…A boy with congenital unilateral microphthalmos presented with an orbital mass with histologic features of pilocytic astrocytoma and/or retinal gliosis. Using light microscopy, low-grade intraocular astrocytoma is indistinguishable from massive retinal gliosis 1, 2, 3, 4…”
Section: Discussionmentioning
confidence: 99%
“…The findings in our patients are consistent with the reactive nature of this tumor, which may occur in a variety of settings. These tumors are slow growing, variably vascularized, and may eventually be classified as massive gliosis of the retina [17]. …”
Section: Discussionmentioning
confidence: 99%
“…These iterative name changes often coincide with histopathologic and molecular diagnostic interpretations of clinically described entities. As has occurred many times in the past, such as for the retinal tumors retinoblastoma and hemangioblastoma, a name change is currently underway for the retinal tumor reactive retinal astrocytic tumor (focal nodular gliosis), formerly known as vasoproliferative tumor [1,2,3]…”
mentioning
confidence: 99%
“…They suggested that these lesions are all interrelated and exist on a continuous spectrum [2]. Hudson and co-workers [3] published the “missing link” case, in which a patient first clinically diagnosed with a “retinal angioma” (focal nodular gliosis) was followed over a period of years during which the tumor slowly progressed; the eye was subsequently enucleated and it was shown to contain massive gliosis. Taken together, it is now clear that retinal reactive astrocytic tumor (focal nodular gliosis) is the preferred name for this entity.…”
mentioning
confidence: 99%